Service design based on social simulation: An integrated experience mapping methodology considering customers and service providers - Kikuchi, Takamasa; Takahashi, Hiroshi (Frontiers in Physics, 2022)
Approaches using both real data and social simulations have been proposed to address economic and social problems. Understanding the structure of models and the results of simulations may be used by not only model developers and analysts but also by decision-makers in management and administration as well as on-site managers. Therefore, (1) methodologies for deriving findings and knowledge from simulation results and (2) a mechanism for propagating the derived findings and knowledge to the parties involved are both required. In this study, we compare log analysis frameworks and create a formal description of social simulations for benefit-delay products and services to determine their merits, shortcomings, and limitations. Then, by extending an experience mapping method from a previous study, we propose a method for also describing a service provider’s experience. We use this method to simulate pre- and post-retirement asset sustainability. The main findings are as follows: (1) an integrated experience description of the customer and provider sides of a benefit-delay service design is feasible, and (2) customer targeting based on this description is possible.